Ethnophysics of Tua Reta Lou Dance: Mapping Equilibrium, Torque, and Circular Motion for Contextual Physics Learning - Dewa, Egidius; Maing, Claudia Mariska M; Ki`i, Oktavianus Ama; Kua, Maria Yuliana; Freitas, Maria Lia Felizarda (Integrated Science Education Journal, 2026)
Purpose of the study: This study explores and identifies physics concepts embedded in the Tua Reta Lou dance as a form of local wisdom from Sikka Regency, East Nusa Tenggara, Indonesia, with a focus on motion-dynamics constructs that can be used as contextual resources for physics learning. Methodology: This study employed a qualitative exploratory (ethnophysics) design. Data were collected through (i) field observations of Tua Reta Lou performances, (ii) photo/video documentation of key movement components and dancer bamboo interactions, and (iii) semi-structured interviews with dancers and cultural practitioners selected using purposive sampling (information-rich participants). Data were analyzed iteratively through qualitative reduction–display–conclusion procedures and analytical mapping of observed phenomena to mechanics constructs. Main Findings: The Tua Reta Lou dance embodies key mechanics concepts, including rigid-body equilibrium and center of mass (balancing on the bamboo tip), torque and rotational equilibrium (force regulation through hands/feet and supporting dancers), moment of inertia (stability strategy via limb extension), and circular motion represented through centripetal force and angular momentum. These concepts are consistently represented through recurrent movement components during the performance. Novelty/Originality of this study: This study provides a structured ethnophysics mapping of Tua Reta Lou into explicit motion-dynamics constructs and outlines a curriculum-aligned pathway to transform local cultural practice into contextual physics learning resources.